Optimizing the Quality of Islamic Education through School Management and Learning Process - Masyhuri, Mochammad Malikul; Sutiah, Sutiah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This article discusses the role of a learning process in order to achieve the goals of a learning program, so it can be said that quality education is determined by several related components, starting from input, process, and output, as well as good management. The learning process today is developing very rapidly due to demands and pressures to improve the quality of education.The research method used in this article is qualitative with a library research approach, because the authors here explore and search for data through research and reading of scientific works that are appropriate to the topic of discussion.The government expects standards in the learning process, namely planning, implementation and assessment. In a quality learning process, various learning inputs are involved, such as: students (cognitive, affective, or psychomotor), learning materials, methodology (varies according to the ability of the teacher), school facilities, administrative support and infrastructure and other resources and the creation of a conducive atmosphere. The results of this research show that managing the quality of Islamic education is not only about meeting formal standards set by the government, but also about creating a learning environment that is conducive, innovative and responsive to students' needs and the demands.